Firm-level conditions to engage in public-private partnerships: what can we learn? - Lopes, A. I.; Caetano, T. T. (Journal of Economics and Business, 2015)
This research examines the firm-level conditions of Portuguese listed companies to be engaged in Public Private Partnerships - Service Concessions Arrangements (PPP/SCAs). Based on accounting standards and other legislation regarding PPP/SCAs, a set of firm’s characteristics was tested in order to find determinants for that engagement. Through empirical evidence it is suggested that larger firms and relative higher leveraged firms attract more PPP/SCA projects. The results also imply that when the most important segment report is coincident with the primary line of business industry, firms have more probability of being engaged with a PPP/SCA. Findings also show that profitability and financing costs (as a proxy for risk) are not robust determinant for attract a PPP/SCA. This paper adds to the scarce (but in a growing phase) literature on the financial reporting of service concessions arrangements, contributing to a better understanding of the extent and conditions behind PPP/SCAs.